2010
DOI: 10.1143/jpsj.79.024006
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Statistical Mechanics and Scaling Behavior for Non-equilibrium Polymer Chains: II. Monomers Connected by Springs

Abstract: Using molecular dynamics simulation, we find that the velocity distributions of monomers in the system of non-equilibrium polymer chains and Lennard-Jones molecules in a wide range of simulation time can be well described by Tsallis q-statistics and a single scaling function; the value of q is related to the conformation constraining potential, the interactions with background fluid, or the destruction of chain homogeneity. This approach can be applied to other non-equilibrium systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
(54 reference statements)
3
21
0
Order By: Relevance
“…9) We have used molecular dynamics (MD) simulations to study relaxation processes in various systems of polymer chains and Lennard-Jones (L-J) molecules; two neighboring monomers along a polymer chain are connected by a rigid bond 10) or a spring of strength k spring . 11) We find that the velocity distributions of monomers in a wide range of simulation time can be well described by Tsallis q-statistics 14), 15) and a single scaling function, where q ≥ 1 and q-statistics becomes the Maxwell-Boltzmann distribution when q → 1. We also find that when neighboring monomers of a polymer chain have small or zero bending-angle and torsion-angle dependent potentials, then the polymer chains tend to aggregate.…”
Section: §1 Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…9) We have used molecular dynamics (MD) simulations to study relaxation processes in various systems of polymer chains and Lennard-Jones (L-J) molecules; two neighboring monomers along a polymer chain are connected by a rigid bond 10) or a spring of strength k spring . 11) We find that the velocity distributions of monomers in a wide range of simulation time can be well described by Tsallis q-statistics 14), 15) and a single scaling function, where q ≥ 1 and q-statistics becomes the Maxwell-Boltzmann distribution when q → 1. We also find that when neighboring monomers of a polymer chain have small or zero bending-angle and torsion-angle dependent potentials, then the polymer chains tend to aggregate.…”
Section: §1 Introductionmentioning
confidence: 77%
“…11) We find that during the relaxation process the velocity distributions of monomers in a wide range of simulation time can be well described by Tsallis q-statistics 14), 15) with a generalized Maxwell-Boltzmann distribution (GMBD) 22)-24) and a single scaling function. The value of q is related to the conformation constraining potential, the interactions with background fluid, the destruction of chain homogeneity or the value of k spring .…”
Section: §1 Introductionmentioning
confidence: 92%
“…Very recently, Ma and Hu [39][40][41][42][43] used MD to study relaxation and aggregation of polymer chains, in which neighboring monomers of a polymer chain are connected by rigid bonds [39,41] or springs with various spring constants [40,42]. They found that when the bending-angle depending potential and the torsion-angle depending potential are zero or very small, polymer chains tend to aggregate [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Over the processes along the red dashed line on the right side of Fig. 1(e), the probability density function P GMB ( v ) for monomer speed v at each instant is well fitted by the generalized Maxwell-Boltzmann (GMB) speed distributionwhere the factor j G ( v ) = 4 πv 2 has been used in previous studies 51, 52 and A q is the normalization factor and all monomers are assumed to have equal masses, m  = 1. Note that, the choice of factor 4 πv 2 is compatible with the isotropic Maxwell’s distribution of speed (subscript ‘IMB’ for istropic Maxwell-Botzmann), which isas the special case of q  = 1.…”
Section: Introductionmentioning
confidence: 95%